TANGGUNG JAWAB PEMEGANG LESSOR ATAS KERUGIAN DEBITUR AKIBAT PENARIKAN OBJEK JAMINAN FIDUSIA SECARA PAKSA (STUDI PUTUSAN NOMOR 35/PDT.G.S/2021/PN PDG) - Nurhaliza, Siti; Rahman, Arif; Nurarafah, Nurarafah (Fakultas Hukum Universitas Malikussaleh, 2025)
The lessor cannot arbitrarily use force and violence to withdraw the fiduciary collateral objects of debtors who are experiencing bad credit problems, as regulated in the Fiduciary Guarantee Law. Decision Number 35/Pdt.G.S/2021/PN Pdg regarding the execution of fiduciary guarantees carried out by force by a third party without showing a withdrawal letter issued by the High District Court. This research aims to find out and explain the impact of forced withdrawal of fiduciary collateral objects on debtors and the basis for the judge's consideration of decision Number 35/Pdt.G.S/2021/PN.Pdg. This research uses a type of normative legal research. The research approach was carried out using a statutory approach. The research results show that the impact of forced withdrawal of fiduciary collateral objects can cause losses to the debtor, in which case the debtor does not receive compensation for the credit installment achievements that have been made and the debtor cannot obtain clear legal protection. The judge's basis for consideration is that in considering the legal basis along with the evidence presented at the trial, it is stated that the claims arguments contained in the lawsuit posita and the demands contained in the lawsuit petitum according to the panel are based on law and do not conflict with the law, so they should be granted in part with without the presence of the defendant (verstek). It is hoped that the lessor will bring in law enforcement officers when towing a motor vehicle, in this case the police.